The academic contributions of Carlos Urzúa - Esquivel, Gerardo (Estudios Económicos de El Colegio de México, 2024)
This article is part of a special section of Estudios Económicos, volume 39, number 2, July-December 2024, dedicated to honoring the memory of the economist Carlos Manuel Urzúa Macías, who passed away on February 19, 2024. In this commemorative section, his colleagues from El Colegio de México, Raymundo M. Campos-Vázquez, Horacio Sobarzo, and Gerardo Esquivel, recall his valuable contributions to both academia and the public sector.